2018
DOI: 10.4274/jcrpe.5043
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis and an Evaluation of Trends in Obesity Prevalence among Children and Adolescents in Turkey: 1990 through 2015

Abstract: ObjectiveObesity in childhood and adolescence is one of the most serious public health problems due to a remarkable increase in prevalence in recent years and its close relationship with non-communicable diseases, such as diabetes and hypertension, resulting in increased adult morbidity and mortality. This study aims to quantify the secular trend in different regions of Turkey from 1990 to 2015 by performing a meta-analysis of childhood and adolescent obesity prevalence studies conducted.MethodsUludag Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 27 publications
1
49
1
5
Order By: Relevance
“…Obesity, with all its attendant comorbidities, is one of the most concerning scenarios of our time, and the number of people with obesity is increasing each day . In the past it had been thought of as a disease of adulthood, but 7.3% of the children in Turkey are now above the obesity cut‐off . Obesity may simply be related to feeding habits, as it is in most cases, but it also may be a result of endocrinological, neurological, metabolic, genetic or psychiatric conditions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity, with all its attendant comorbidities, is one of the most concerning scenarios of our time, and the number of people with obesity is increasing each day . In the past it had been thought of as a disease of adulthood, but 7.3% of the children in Turkey are now above the obesity cut‐off . Obesity may simply be related to feeding habits, as it is in most cases, but it also may be a result of endocrinological, neurological, metabolic, genetic or psychiatric conditions .…”
Section: Discussionmentioning
confidence: 99%
“…8 In the past it had been thought of as a disease of adulthood, but 7.3% of the children in Turkey are now above the obesity cut-off. 9 Obesity may simply be related to feeding habits, as it is in most cases, but it also may be a result of endocrinological, neurological, metabolic, genetic or psychiatric conditions. 1 In the present study, only one of the patients had proven Bardet-Biedl syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several reports which have shown a plateau or a decreasing trend of childhood OW and OB in recent years from some regions of European countries (England (10), Ireland (11), France (12), Sweden (13), Italy (14) and Germany (15), Australia (16) and United States (17)); globally, the prevalence of OW and OB is rising among children and adolescents in both developed and developing countries, as is the case in Turkey (2) (4) (18). Alper et al [4] showed in a meta-analysis that the overall prevalence of OB in Turkey is 7.3 % among school aged children (6.8 % in girls, 7.4 % in boys). However, the prevalence of OW and OB in our study was significantly higher than other regions in Turkey (4), (5), (19), (20).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Today, changes in lifestyle habits, including nutrition and physical activity habits, that the prevalence of obesity for public health caused a signifi cant increase in the last 20 years considered to be a serious threat in Turkey [1,2]. In order to stop this increase, it is recommended to provide public health education including balanced nutrition and physical activity [2].…”
Section: Introductionmentioning
confidence: 99%